Not yet queer, here and now for sexualities and schooling*. Issue 3 (4th May 2018) - Coll, Leanne; Charlton, Emma
Abstract: This paper represents our collective engagements and productive struggles with queer pedagogical-methodological (im)possibilities across a constellation of educational contexts. Following in the footsteps of queer theorists-pedagogues before us, we approach queerness as a horizon, a unique opportunity to experiment, take risks, explore new forms of undoing and to move-be-think-do otherwise. We begin by attending to the ways in which researchers-educators in the field of sexualities and schooling are pushing these conversations forward, followed by two vignettes from our own work. Our intention in sharing these vignettes is to slow down and expose some of the methodological-pedagogical processes that guide our work, our attempts to stay in the moment that trouble creates, and the challenge of staying in that moment to learn from it. This paper suggests that embracing new forms of enquiry, which account for queer methodological-pedagogical sensibilities, requires researchers-educators to actively embrace the failures of their own practice and engage with the contestations of theories that matter/materialise.